PATHOLOGICAL EFFECT OF CITRININ AND AFLATOXIN IN BROILER CHICKEN: Pharmaceutical Science-Pathology - ANAND KUMAR, THEOPHILUS; C. BALACHANDRAN (International Journal of Life Science and Pharma Research, 2014)
The individual and combined pathological effects of citrinin (CTN) at 5 ppm and aflatoxin (AF) at 0.5 ppm were studied in broiler chicken by feeding the mycotoxins from 0 to 6 weeks of age. In the entire toxin fed groups, inappetance and brownish diarrhoea were observed from first week onwards. The AF and CTN+AF fed groups showed ruffled feathers, lethargy, and stunted growth from the third week. There was no mortality in the control and mycotoxin fed groups. There was a significant (P<0.05) increase in the relative weight of the liver and spleen and decrease in the bursa of Fabricius in the entire mycotoxin treated groups when compared to the control group. In birds fed with CTN, the liver showed congestion, enlargement, pallor or yellowish discolouration and distended gall bladder. Kidneys revealed swelling, congestion and a few petechiae. Splenomegaly, atrophy of the bursa of Fabricius and catarrhal enteritis was also observed. In the AF group, the lesions were severe, affecting all birds. The gross lesions were pronounced in the sixth week. Microscopically, glomerular basement membrane thickening, degeneration and necrotic changes in the tubular epithelial cells in kidneys, degenerative changes in hepatocytes, microgranuloma, periportal fibrosis, periductular mononuclear cell infiltration, fatty degeneration, focal necrosis and fibrosis in the liver, mucosal hyperplasia of crop, proventriculitis, ventriculitis, catarrhal enteritis, pancreatitis, myocardial degeneration, mycocarditis, hyaline degeneration of muscle, lymphoid depletion and atrophic changes in the bursa of Fabricius, lymphoid depletion and reticulum cell hyperplasia in spleen, lymphoid depletion in caecal tonsils and plasma cell depletion in the Harderian gland were observed in the mycotoxin fed birds. Combined toxicity was more severe when compared to the individual mycotoxin fed groups. However, the effect was less than additive.